Kurpe O.G., Kukhar V.V., Zmazneva E.V. Calculation refinement of metal heat loses on the Steckel rolling mills. - Курпе, О. Г.; Кухар, В. В.; Змазнева, Є. В. (Problems of Tribology, 2018)
The thesis improves the calculation methodology of metal heat loss during hot rolling procedure at Steckel mills. The proposed methodology can be implemented at different complexes on the Steckel mill base at all temperature ranges and modes of hot rolling production for carbon and microalloying steel grades. It offers engineering analysis of unaccounted temperature losses of feed by means of radiation and convection, which, in the first time, through the time factor, additionally accounts for strip motion speed factors, roller table length, and also length of rolls contact arc with metal. Regular links between these factors, time spent and value of heat loss, were previously unknown. So the calculation under the available methodologies resulted in significant measures of inaccuracy. The accountability of the above mentioned factors increases the engineering simulation accuracy, ensures the versatility of the elaborated method with respect to different types of Steckel mills and makes the scientific novelty of the study. The formula was developed to calculate the temperature loss while space coiling at the furnace coiler. In the first time the formula accounts for the influence on the temperature of such variables as strip thickness and length, coiling speed, temperature of metal before furnace coiler, inside diameter of the furnace reeling. The calculation of the temperature change was made within one-sided heating of the thermally thin body during the period equal to reeling of the last wrap onto the drum, and this is the remarkable novelty and the academic novelty. The improved model was verified based on actual data from Steckel rolling mill, Ferriera Valsider SpA shop (metallurgical shop successful working in Verona province, Italy, part of the Metinvest Group since 2001). The improved model can be used for hot rolling process technology simulation at the Steckel mills with various in-line equipment arrangement.